The complete genome sequence of Ethanoligenens harbinense reveals the metabolic pathway of acetate-ethanol fermentation: A novel understanding of the principles of anaerobic biotechnology. (October 2019) - Li, Zhen; Liu, Bingfeng; Cui, Han; Ding, Jie; Li, Huahua; Xie, Guojun; Ren, Nanqi; Xing, Defeng
Abstract: Ethanol-type fermentation is one of three main fermentation types in the acidogenesis of anaerobic treatment systems. Non-spore-forming Ethanoligenens is as a typical genus capable of ethanol-type fermentation in mixed culture (i.e. acetate-ethanol fermentation). This genus can produce ethanol, acetate, CO2, and H2 using carbohydrates, and has application potential in anaerobic bioprocesses. Here, the complete genome sequences and methylome of Ethanoligenens harbinense strains with different autoaggregative and coaggregative abilities were obtained using the PacBio single-molecule real-time sequencing platform. The genome size of E. harbinense strains was about 2.97–3.10 Mb with 55.5% G+C content. 3020–3153 genes were annotated, most of which were methylated at specific sites or motifs. The methylation types included 6mA, 4mC, and unknown types. Comparative genomic analysis demonstrated low levels of genetic similarity between E. harbinense and other well-known hydrogen-producing bacteria (i.e., Clostridium and Thermoanaerobacter ) in phylogenesis. Hydrogen production of E. harbinense was catalyzed by genes that encode [FeFe]‑hydrogenases and that were synthesized by three maturases of [FeFe]-H2 ase. The metabolic mechanism of H2 -ethanol co-production fermentation, catalyzed by pyruvate ferredoxin oxidoreductase was proposed. This study provides genetic and evolutionary information of a model genus for the further investigation of the metabolic pathway and regulatory network of ethanol-type fermentation and anaerobic bioprocesses for waste or wastewater treatment. Graphical abstract: Unlabelled Image Highlights: Complete genome sequences of Ethanoligenens harbinense were assembled. DNA methylation of E. harbinense included 6mA, 4mC, and unknown types. Comparative genomics showed low similarity between E. harbinense and Clostridium . Pyruvate ferredoxin oxidoreductase is important for H2 -ethanol co-production. The genetic and evolutionary information of E. harbinense is provided.